Life‐cycle responses of a Mediterranean non‐migratory cyprinid species, the Northern Iberian chub (Squalius carolitertii Doadrio, 1988), to streamflow regulation. - Alexandre, C.M. (2018)
Streamflow is considered a driver of interspecific and intraspecific life‐history differences among freshwater fish. Therefore, dams and related flow regulation can have deleterious impacts on their life cycles. The main objective of this study was to assess existing differences in the growth and reproduction patterns of a non‐migratory fish species (the Northern Iberian chub, Squalius carolitertii, Doadrio, 1988), between nonregulated and regulated watercourses. For 1 year, samples were collected from two populations of Iberian chub, inhabiting rivers with nonregulated and regulated flow regimes. Flow regulation for water storage promoted changes in chub's condition, duration of spawning, fecundity, and oocyte size. However, this non‐migratory species was less responsive to streamflow regulation than other native potamodromous species. Findings from this study are important to understand changes imposed by regulated rivers and can be used to support the implementation of suitable river management practices.